2005
DOI: 10.1111/j.1601-1546.2005.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical preparation of root canals: shaping goals, techniques and means

Abstract: Preparation of root canal systems includes both enlargement and shaping of the complex endodontic space together with its disinfection. A variety of instruments and techniques have been developed and described for this critical stage of root canal treatment. Although many reports on root canal preparation can be found in the literature, definitive scientific evidence on the quality and clinical appropriateness of different instruments and techniques remains elusive. To a large extent this is because of methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
699
0
91

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 715 publications
(801 citation statements)
references
References 351 publications
(531 reference statements)
11
699
0
91
Order By: Relevance
“…Generally, the high chip space of an instrument improves its debris removal capacity (15). Previous researches have shown that instruments with active cutting-edge blades had superior cleaning efficiency compared to radial lands (6,28,29). Thus, lower PT results could be explained by the presence of the convex flutes of the triangular cross-section that are not found on the PTN and R instruments ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the high chip space of an instrument improves its debris removal capacity (15). Previous researches have shown that instruments with active cutting-edge blades had superior cleaning efficiency compared to radial lands (6,28,29). Thus, lower PT results could be explained by the presence of the convex flutes of the triangular cross-section that are not found on the PTN and R instruments ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, these methods cannot completely remove the smear layer, preventing the penetration of chemical irrigating solutions into dentinal tubules [6,10], leading to, as a consequence, less than full elimination of nested bacteria [4,11,12]. In fact, the method is mostly limited to a dentin depth between 100 and 300 μm.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies [6][7][8][9] have shown that bio-mechanical, also known as chemo-mechanical, methods play a significant role in the treatment of root canal systems. On the one hand, these methods cannot completely remove the smear layer, preventing the penetration of chemical irrigating solutions into dentinal tubules [6,10], leading to, as a consequence, less than full elimination of nested bacteria [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…(1988) permitiu melhoras significativas no preparo químico-cirúrgico do SCR uma vez que é possível sua utilização na instrumentação dos canais radiculares curvos com a manutenção do formato anatômico do canal e com a redução na formação de degraus ou zips e no transportes de forames (Bergmans et al, 2001;Hulsmann et al, 2005;Yoshimine et al, 2005). (Bourauel et al, 1998).…”
Section: Discussionunclassified
“…As limas de NiTi proporcionam um preparo cêntrico, com menor incidência de transporte do canal e formação de degraus, o que resulta na conservação da forma anatômica original (Bergmans et al, 2001;Hulsmann et al, 2005;Yoshimine et al, 2005).…”
Section: Instrumentos Endodônticos De Nitiunclassified